Language Maintenance of Bahasa Tansi - Zahra, Salsabillah Vatia; Arianto, M. Affandi (English Language and Literature, 2024)
This study aimed to find out whether Tansi speakers still maintain their language and the efforts made by Tansi speakers to maintain it. Using mixed methods,this research analyzed the similarities and differences between the Minangkabau and Tansi languages and identify factors that influence maintenance and intutional maintenance. Ten data sources in this research came from the Tansi community in Tangsi Baru (Lembah Segar District) and Sikalang Village (Talawi District).In conclussion, Tansi is still widely and consistently used in homes and among family speakers. In addition, speakers actively teach Tansi to their children, indicating an awareness of language maintenance. Although initiatives such as language contests and local government support for language maintenance are present, they are still not systematic enough. Thus, maintaining the continuity of the Tansi language outside the family environment must continue to be done in order to maintain the Tansi language for the next generation.